Endoscopists can sustain high performance for the optical diagnosis of colorectal polyps following standardized and continued training - McGill, Sarah K.; Soetikno, Roy; Rastogi, Amit; Rouse, Robert V.; Sato, Tohru; Bansal, Ajay; McQuaid, Kenneth; Kaltenbach, Tonya (Endoscopy, 2015)
Background and study aims: The learning curve for optical diagnosis of colorectal polyps with the narrow-band imaging (NBI) is unknown. To forego histological analysis of diminutive polyps diagnosed optically with high confidence, guidelines recommend ≥ 90 % negative predictive value (NPV) and concordance of ≥ 90 % for surveillance intervals predicted optically and histologically. We aimed to study the learning of optical diagnosis for colorectal polyps.Patients and methods: We studied five endoscopists as part of a randomized multisite trial comparing near-focus and standard-focus views for optical diagnosis. They trained using a computer-based module, followed by 10 real-time colonoscopies with pathology correlation. Endoscopists then optically diagnosed and resected all the polyps found during 558 consecutive colonoscopies, and diagnoses were compared with pathology. Endoscopists repeated the training module at the study midpoint. NPV and concordance of surveillance intervals for diminutive polyps diagnosed optically with high confidence were measured over time. Results: Endoscopists showed high diagnostic performance, with a nonsignificant trend toward higher NPV in the second half of the study. For the 445 polyps in the standard-view arm, the NPV was 88.0 % (95 %CI 75.7 % – 95.5 %) in the first half and 95.8 % (88.3 % – 99.1 %) in the second; P = 0.7. Three endoscopists in the first half and four in the second achieved > 90 % NPV. Concordance of surveillance intervals was identical in the first and second halves at 98.1 % (95 %CI 93.3 % – 99.8 %).Conclusions: High NPV for the prediction of non-neoplasms with NBI was achieved and maintained in this group of endoscopists who participated in standardized and continued training. Both NPV and surveillance interval agreement indicated high performance in the optical diagnosis of colorectal polyps and exceeded thresholds.